Wireless communications and networks - Stallings, William; Stallings, William (Upper Saddle River, NJ : Pearson Prentice Hall, 2005)
Learn all about satellite parameters and configuration, principles of cellular networks, wireless local loops, message authentication, transmission fundamentals, antennas and propogation, signal encoding techniques, spread spectrum, coding and error control, and related topics.
Rev. ed. of : Wireless communications and networking, Pearson Prentic Hall, 2002.
Includes bibliographical references (p. 540-546) and index.
Keywords: Wireless communication systems; Wireless LANs